2008
DOI: 10.1080/00016480701558948
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of cochleotoxicity among three gentamicin compounds following intratympanic application

Abstract: The ABR threshold of the C2 group was found to be more impaired than those of the other groups. The C1a group showed the mildest elevation of the ABR thresholds. Morphological analyses revealed that the proportion of remaining outer hair cells (OHCs) was the lowest in animals treated with C2. Morphologically, the C1 and C1a groups showed the least damage to OHCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…However, application of gentamicin could lead to hearing disturbances [12]. If the application of Omniscan could lead to only vestibular depressants without cochlear damage, control of vertiginous attacks without hearing disturbance would be possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, application of gentamicin could lead to hearing disturbances [12]. If the application of Omniscan could lead to only vestibular depressants without cochlear damage, control of vertiginous attacks without hearing disturbance would be possible.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have received much attention in recent years as a broad-spectrum antibiotic for the treatment of various infections as well as a promising drug lead for the treatment of several inherited diseases and a sensitizing agent for lung cancer cells 2426 . Gentamicin contains the core 2-DOS moiety with the amino-sugars purpurosamine and garosamine attached at positions C4 and C6, respectively.…”
Section: Parallel Pathways In Gentamicin Biosynthesismentioning
confidence: 99%
“…Milovic et al reported that in cispaltin-based chemotherapy followed by antibiotic treatment with aminoglycosides, gentamicin showed higher nephrotoxicity than amikacin with a closely related chemical structure [6]. These results proposed that the similar and/or slightly different structures would produce variant biological effects such as those of gentamicin components C1a, C2/2a and C1 [7]. Thus, there is an important work needed to separate and/or isolate the gentamicin components from the mixture for biological researches.…”
Section: Introductionmentioning
confidence: 95%